Effects of land use on soil microbial community function in western Kenya highlands - Pallarès Vinyoles, Glòria (2008)
Land degradation, agricultural intensification and deforestation may result in a loss of soil microbial community function, detrimental to resilience and to sustained productivity. In order to assess the effects of land use on microbial community function in a tropical soil the following hypotheses were considered: (1) functional capacity measured as substrate-utilization potential decreases with intensification of land use and (2) tree planting - i.e. as used in agroforestry - is a soil conservation and improvement measure which can restore physical, chemical and biological properties of degraded and overused soils.